THE PROBLEM OF ENFORCEABILITY OF MEDIATION AGREEMENTS IN FAMILY CASES: DE LEGE LATA AND DE LEGE FERENDA - Shokirova , Diyorakhon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article examines one of the key theoretical and practical issues of mediation in the field of family law—the enforcement of mediation agreements. It analyzes the existing legal regulation (de lege lata) in the Republic of Uzbekistan and several foreign legal systems, identifying systemic gaps and conflicts that hinder the effective implementation of mediation agreements in family disputes. Based on comparative legal methods and doctrinal analysis, the author proposes recommendations for improving legislation (de lege ferenda) aimed at establishing a reliable legal mechanism for the compulsory enforcement of mediation agreements in family cases.